2019
DOI: 10.4103/jfmpc.jfmpc_176_19
|View full text |Cite
|
Sign up to set email alerts
|

Medication concordance in modern medicine – A critical appraisal from an Indian perspective

Abstract: Modern medicine encompasses a holistic approach toward patient care that seeks to integrate the social, psychological, and pathological aspects of a disease. In line with this, the traditional model of improving treatment outcomes through improved compliance or adherence has given way to the concept of “concordance” that respects the integrity of the patient, autonomy, and self-determination. A self-conscious patient actively and equally participating in her or his comprehensive healthcare can bring a paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…For example, a participant may voluntarily accept the first dose of the COVID-19 vaccine, believing that the benefits of the vaccine outweigh the risk of taking it; however, the later experience after vaccination, such as having side effects, may alter beliefs and make people more hesitant for subsequent vaccinations. Previous studies have found that patients’ beliefs about medications explain a significant part of the variation in medication nonadherence and refusal [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a participant may voluntarily accept the first dose of the COVID-19 vaccine, believing that the benefits of the vaccine outweigh the risk of taking it; however, the later experience after vaccination, such as having side effects, may alter beliefs and make people more hesitant for subsequent vaccinations. Previous studies have found that patients’ beliefs about medications explain a significant part of the variation in medication nonadherence and refusal [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient has to pay the excess amount (the difference in cost between the preferred and the reference drug). This can be included as a part of medication concordance in regular clinical practice, which is based on shared decision making between the doctor and the patient [25]. Many countries are using this strategy to attenuate increased pharmaceutical spending [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, medication adherence is "the extent to which a patient follows a prescription through his or her decision about medicine-taking". 1 With an increasing prevalence of chronic diseases, adherence to therapy has become more challenging as studies indicate that adherence rates vary over time and are generally lower than satisfactory. 2 In a meta-analysis conducted to assess the prevalence of primary medication non-adherence seen with new prescriptions in six common chronic diseases was calculated as 17% using a random-effects model.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the realms of cutting‐edge healthcare technology, developed infrastructure and high efficacy drugs, adherence to medication is a basic, low‐cost, behaviour driven, bipartite patient‐doctor endeavour that can considerably ameliorate disease progression, decrease morbidity‐mortality and reduce health care costs. By definition, medication adherence is “the extent to which a patient follows a prescription through his or her decision about medicine‐taking” 1 . With an increasing prevalence of chronic diseases, adherence to therapy has become more challenging as studies indicate that adherence rates vary over time and are generally lower than satisfactory 2 .…”
Section: Introductionmentioning
confidence: 99%